Positive Politeness Performed by Paul Pogba in the Muslim Money Experts Podcast - Yuliani, Syafhara Dewi; Wardoyo, Cipto; Ardiansyah, Erlan Aditya (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2024)
This study examines the use of positive politeness strategies and the factors that influence the use of positive politeness strategies in the speech of a Muslim football player, Paul Pogba, in The Muslim Money Experts Podcast Episode 3. This study uses the theory of positive politeness strategies proposed by Brown and Levinson (1987) as a tool to answer the problem formulation. The method used in this research is a descriptive qualitative approach that examines various things with a natural background to try to understand or interpret various phenomena. Based on the findings in this study, we found that 194 data from 15 positive politeness strategies were used by Paul Pogba. There are 29 data of the most dominant of two sub-strategies, the first, intensify interest to the H, because Paul Pogba wants to involve hearers in the topic he is talking about and wants to increase hearers’ interest in a topic, and the second sub-strategy, presuppose/raise/assert common ground, because Paul tries to build cooperation with hearers. The least used sub-strategy is a joke. Keywords: Positive Politeness Strategies, Paul Pogba, Muslim Football Player